2005
DOI: 10.1152/ajplung.00210.2005
|View full text |Cite
|
Sign up to set email alerts
|

Activation of endothelial NADPH oxidase during normoxic lung ischemia is KATP channel dependent

Abstract: Previous studies have shown endothelial cell membrane depolarization and generation of reactive oxygen species (ROS) in endothelial cells with abrupt reduction in shear stress (ischemia). This study evaluated the role of ATP-sensitive potassium (K(ATP)) channels and NADPH oxidase in the ischemic response by using Kir6.2-/- and gp91(phox)-/- mice. To evaluate ROS generation, we subjected isolated perfused mouse lungs labeled with 2',7'-dichlorodihydrofluorescein (DCF), hydroethidine (HE), or diphenyl-1-pyrenylp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(103 citation statements)
references
References 32 publications
(61 reference statements)
8
95
0
Order By: Relevance
“…Isolated Lung Perfusion-The isolated perfused mouse lung technique has been described previously (11). Briefly, mice were anesthetized with 50 mg/kg intraperitoneal sodium pentobarbital, and the lungs were cleared of blood and then removed from the thorax and placed in a perfusion chamber.…”
Section: Methodsmentioning
confidence: 99%
“…Isolated Lung Perfusion-The isolated perfused mouse lung technique has been described previously (11). Briefly, mice were anesthetized with 50 mg/kg intraperitoneal sodium pentobarbital, and the lungs were cleared of blood and then removed from the thorax and placed in a perfusion chamber.…”
Section: Methodsmentioning
confidence: 99%
“…These NOX's appear to control several vascular processes, such as vascular tone, vascular cell growth and angiogenesis, and inflammation. Accordingly, pulmonary endothelial cells have been demonstrated to generate NADPH-derived oxidants in response to pulmonary ischemia (178,179) as well as hyperoxia (180), which is associated with membrane depolarization due to the activation of K(ATP) channels, and resulting in stimulated endothelial cell proliferation and NO production (178,181,182). Although these responses were in some cases inhibited by catalase, suggesting the involvement of H 2 O 2 (182), recent studies also suggest a role for O 2 •− in endothelial NOX signaling (77).…”
Section: Functional Aspects Of Nox In Other Lung Cell Typesmentioning
confidence: 99%
“…ROS can signal to the nucleus and control gene expression to regulate cell metabolism appropriately (Finley and Haigis, 2009). The potential effects of two major intracellular sources of ROS on generation of DAergic cells were investigated in the present study: the NADPH oxidase complex and mito-KATP channels, which have also demonstrated a ROS-mediated relationship (Kimura et al, 2005a,b;Zhang et al, 2005;Sheh et al, 2007;Alberici et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…ROS open up KATP channels (Zhang et al, 2002;Avshalumov and Rice, 2003), and mitochondrial ROS production can be stimulated by the opening of mitochondrial mitoKATP channels (Costa and Garlid, 2008;Kimura et al, 2005b). Recent studies have shown a ROSmediated relationship between the NADPH oxidase complex and the mitoKATP channels (Kimura et al, 2005a;Zhang et al, 2005;Sheh et al, 2007;Alberici et al, 2009) and that events leading to mitochondrial dysfunction or increased cytoplasmatic ROS have a significant upstream impact on increasing NADPH activity (Li et al, 2001;Wosniak et al, 2009). This suggests cross-talk signaling between both systems (reviewed by Daiber, 2010).…”
Section: Introductionmentioning
confidence: 99%